PERANCANGAN WEBSITE SMART SCHOOL SYSTEM SEBAGAI MEDIA INFORMASI DAN KOMUNIKASI DIGITAL DI SDN DANUKUSUMAN - Putra Setiawan, Praditia; Trisiana, Anita; Pandu Widhoyoko, Yudhistiro (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This research aims to design and develop the Smart School System website portal at SDN Danukusuman Surakarta as a centralized, structured, and dynamic digital information and communication medium. The research method used is Research and Development (R&D), applying the ADDIE (Analysis, Design, Development, Implementation, Evaluation) development model. The system was built independently using the PHP Native programming language, a MySQL database integrated through XAMPP, and was supported by Unified Modeling Language (UML) blueprints and the Bootstrap framework to produce a responsive interface. The results of the technical feasibility testing using Black Box Testing through a questionnaire instrument assessment by three media expert lecturers obtained an average percentage of 92%, qualifying as "Highly Feasible." Meanwhile, the assessment by three material experts (Principal, Operator, and Teacher) yielded an average percentage of 93.33%, qualifying as "Highly Feasible." The evaluation of the user acceptance rate using the Technology Acceptance Model (TAM) distributed to student parent representatives also resulted in an average percentage of 93.33% ("Highly Feasible"). These overall results indicate that the developed Smart School System website is highly feasible and effective for use as a digital communication medium to bridge the information gap between the school and the public, as well as to optimize the efficiency of school data management in real-time.